Ah, but your land is beautiful - Paton, Alan 1903-1988 (Scribner, 1982)
Set in contemporary South Africa, this novel examines the day-to-day experiences of men and women whose lives reflect the human cost of living under the constraints of apartheid.
Keywords: Geschichte 1952-1958; Race relations -- Fiction; Südafrika (Staat); South Africa -- Fiction; Südafrika; Fiktionale Darstellung